A Covenant Reading of the Warning Passage in Hebrews 6: 4-8 - JIANG , Tian (Journal of Research for Christianity in China (JRCC), 2023)
The warning passages in Hebrews demonstrate the two sides of salvation - redemption and judgment - a dichotomy consistent with the covenant model. The primary debate among scholars over these warning passages is whether Christians will lose their salvation. Hebrews 6:4-8 is the center of all warning passages, and interpretations of these passages are divided into two leading schools of thought, Arminianism and Calvinism. This paper attempts to combine the Arminian and Calvinist readings of the warning passages through the lens of covenant theology and to demonstrate that the warning passages in Hebrews are the same as the warning passages elsewhere in the New Testament, which uses the Old Testament covenant model. The New Testament authors imitated the Old Testament prophets in warning the covenant people, both community and individual, not to bring judgment but to call for repentance. The prophetic warning passages in Hebrews are not a judgment on the apostate's final state of salvation, but a call to repentance.